2007
DOI: 10.2337/db06-1135
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Mitochondrial Biogenesis Is Suppressed in db/db and High-Fat Diet–Fed Mice and Improved by Rosiglitazone

Abstract: The objective of this study was to further establish and confirm the relationship of adipose mitochondrial biogenesis in diabetes/obesity and the effects of rosiglitazone (RSG), a peroxisome proliferator-activated receptor (PPAR) ␥ agonist, by systematically analyzing mitochondrial gene expression and function in two mouse models of obesity and type 2 diabetes. Using microarray technology, adipose mitochondrial gene transcription was studied in db/db, high-fat diet-fed C57BL/6 (HFD) and respective control mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
239
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(265 citation statements)
references
References 52 publications
23
239
1
2
Order By: Relevance
“…Regulation of BNIP3 during adipocyte remodelling, especially in obesity or PPARγ-related conditions The role of BNIP3 has been mostly investigated in myocytes in relation to hypoxia-induced apoptotic cell death and autophagic cell survival [14]. Here, we revealed that a considerable amount of BNIP3 expression is regulated in adipocytes under conditions in which higher mitochondrial content is required, including adipocyte differentiation [10], starvation [25] and in BAT [26], and also by rosiglitazone treatment [2,7,10]. We also found that BNIP3 was downregulated in adipose tissue under obese diabetic conditions.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Regulation of BNIP3 during adipocyte remodelling, especially in obesity or PPARγ-related conditions The role of BNIP3 has been mostly investigated in myocytes in relation to hypoxia-induced apoptotic cell death and autophagic cell survival [14]. Here, we revealed that a considerable amount of BNIP3 expression is regulated in adipocytes under conditions in which higher mitochondrial content is required, including adipocyte differentiation [10], starvation [25] and in BAT [26], and also by rosiglitazone treatment [2,7,10]. We also found that BNIP3 was downregulated in adipose tissue under obese diabetic conditions.…”
Section: Discussionmentioning
confidence: 87%
“…Within adipocytes, mitochondria show robust changes in density and morphology under pathophysiological conditions [2,3]. Excess mitochondria occur with myopathy or cancer [4] and reduced mitochondria number and/or function is associated with obesity [5][6][7]. This suggests that tight quality control of the mitochondria may be critical for maintaining adipocyte function during adipocyte remodelling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced mitochondrial mass and function has been found in adipose tissue of ob/ob and db/db mice and in adipose tissue from obese individuals with type 2 diabetes in association with increased activity of several inflammatory pathways [18][19][20][21][22][23][24]. Given previous findings in whole adipose tissue, we hypothesised that iron might have an important role in adipogenesis, and we decided to explore in greater depth which cells are responsible for the altered expression of genes involved in iron metabolism and to investigate the precise role of iron in adipocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…These findings seem to contrast with the general mitochondrial dysfunction described previously in the WAT of HFD-fed mice, or in mice with altered leptin signaling, such as ob/ob and db/db obese mice. [16][17][18] However, it could be considered that a global decline in mitochondrial content would require not only WAT expansion, but also the development of an obesity-driven inflammatory milieu provoked by HFD/ nutrient overload. Indeed, inflammatory mediators are associated with a decline in mitochondrial content 17,[19][20][21] and presumably this inflammatory process does not occur-or occurs to a lesser extent-in aging WAT.…”
Section: Mitochondrial Complex IV Vulnerability In Aging White Adipocmentioning
confidence: 99%